The Role of The Entangled Brain Concept in Unraveling The Complexity of Decision Making and Communication In The Metaverse - Amalia, Putri Chaerani (Green Publisher Indonesia, 2025)
Acquiring a significant understanding of customer behavior, particularly in the decision-making process related to material in the metaverse, is crucial for developing efficient digital marketing strategies. This study employs the notion of the entangled brain as its primary theoretical foundation. This study investigates the influence of the brain's intricate, non-linear, and mutually reinforcing processes on consumer decision-making while also considering determinism, libertarianism, and compatibility. This study suggests that decision outcomes exhibit unpredictability akin to quantum processes by emphasizing the parallels between quantum entanglement and brain activity. Accordingly, this study emphasizes the challenges of predicting human behavior, especially in emerging technologies like the metaverse, where uncertainty can highly occur. Thus, this study offers a theoretical framework combining deterministic and probabilistic perspectives and useful insights about understanding consumer behavior in dynamic digital environments. This study improves our understanding of decision-making processes, emphasizing the significance of adaptable strategies for navigating complex consumer settings.